RNA secondary structure prediction using an ensemble of two-dimensional deep neural networks and transfer learning - Jaswinder Singh (Nature Portfolio, 2019)
The limited availability of high-resolution 3D RNA structures for model training limits RNA secondary structure prediction. Here, the authors overcome this challenge by pre-training a DNN on a large set of predicted RNA structures and using transfer learning with high-resolution structures.